If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xa = ba + c Solving ax = ab + c Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1ab' to each side of the equation. -1ab + ax = ab + -1ab + c Combine like terms: ab + -1ab = 0 -1ab + ax = 0 + c -1ab + ax = c Combine like terms: c + -1c = 0 -1ab + ax + -1c = 0 The solution to this equation could not be determined.
| ln(x-1)=0 | | bx+c=ax | | 7x^3=0 | | =4x-2x+y+6y | | 3x^2+27-30=0 | | 2a-4=132 | | 1x^2-12x+36=0 | | x(x^2)=0 | | x^2+576=10x | | x^2+576=10x^2 | | x+24=10x^2 | | x-x=y | | x-3=y | | 96-5x=7x+54 | | 19x^2+19x+12=0 | | -6w=-8 | | x^2=4x+4+100 | | 4y=256 | | 3y-1=(10y-18)/2 | | (3y-1)/2=(10-18) | | (3y-1)=2(10-18) | | 2(3y-1)=10-18 | | (8x-3)=3(5x+6) | | 3(8x-3)=5x+6 | | 8k-6k+3k= | | x+(x-6)=32 | | 32*2=64 | | ln(x-2)+ln(2x+1)=5 | | b(b-6)=27 | | 3a^2b+2a^2b^2=ab^2+a^2b^2 | | b^2=5b | | 11x+8=129 |